2019
DOI: 10.22395/rium.v18n35a8
|View full text |Cite
|
Sign up to set email alerts
|

Tendencias tecnológicas de depuración de lixiviados en rellenos sanitarios iberoamericanos

Abstract: Este artículo identifica y analiza las tendencias en los enfoques y tecnologías de depuración del lixiviado utilizadas a nivel mundial e implementadas en rellenos sanitarios Iberoamericanos. Se utilizó una metodología de búsqueda sistemática de literatura entre los años 1990-2016. Se empleó también un índice de frecuencia de citación bibliográfica con el fin de establecer un orden de importancia promedio mediante cuartiles (Q) para los enfoques y tecnologías detectadas en las bases de datos consultadas. Los re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 14 publications
(25 reference statements)
0
2
0
Order By: Relevance
“…A global comparative analysis with mature landfills [4,[40][41][42][43][44][45][46] showed that, on average, the BOD 5 (32.8-19,402 mg/L) and COD (2198-32,358 mg/L) concentrations in the study landfill were within the same range of variation (Table 1). However, concentrations of NH 4 , Cd, Hg, and Pb were, on average, 3.22, 1.21, 6.26, and 4.13 times higher compared to reference landfills, respectively.…”
Section: Untreated Leachatementioning
confidence: 99%
“…A global comparative analysis with mature landfills [4,[40][41][42][43][44][45][46] showed that, on average, the BOD 5 (32.8-19,402 mg/L) and COD (2198-32,358 mg/L) concentrations in the study landfill were within the same range of variation (Table 1). However, concentrations of NH 4 , Cd, Hg, and Pb were, on average, 3.22, 1.21, 6.26, and 4.13 times higher compared to reference landfills, respectively.…”
Section: Untreated Leachatementioning
confidence: 99%
“…erefore, this is a global environmental problem and adequately addressing, managing, and disposing of this waste pose enormous challenges [3][4][5]. In this context, solid waste management plays a vital role in urban planning [6,7]; in developing countries, the most economical technique for the final disposal of solid waste is landfills [8,9].…”
Section: Introductionmentioning
confidence: 99%